Die cromerzeitlichen Bären aus der Einhornhöhle bei Scharzfeld - Schütt, Gerda (Hannover : Universität Hannover. Institut für Geologie und Paläontologie, 1968)
Up to now the bear remains from the "Einhornhöhle,, Cave near Scharzfeld at the foot of the Harz Mountains have been aseribed to the species "Ursus spelaeus" without undertaking comprehensive studies. Owing to an erroneous Classification of the gravel deposits covering part of the cave floor into the Middle Terrace of the Oder Rivulet, the fossil-bearing strata have been assigned to the Eemian Interglacial. RODE, who included a part of the Scharzfeld teeth in his treatise on teeth of the bears, has stated arctoidal features in their formation apart from certain specializations. He arrived at the conclusion that the Scharzfeld Bear differs more pronouncedly from all Central European Cave Bears he had investigated than the same differ from each other, and he named the Scharzfeld Bear: "Ursus spelaeus var. hercynica". The geological exploration of the Einhornhöhle Cave and of its environs carried out by DUPHORN in 196? resulted in the aforesaid gravels pertaining to a terrace of a Pre-Elster- Glaciation age; according to DUPHORN the fossil-bearing Sediments were deposited in a Pre-Elster-Glaciation ffarm- Climate Period. The very sparse aceompanying fauna does not contain any Stratigraphie key form; arctic elements and members of an interglacial forest fauna are missing. Its composition teils in favour of a dry, yet not too cool period of the Pleistocene, which is younger than the Villa- franchium. Consequently the cave must have been taken pos- session of for settling in the Cromerian Interglacial. The investigation of the bear remains has led to the result that, in all systematically .important teeth and skeleton characteristics, the Scharzfeld Bear shows either concor- dance with Ursus deningeri or greater analogy to the same than to Ursus spelaeus; in a few properties it even appears somewhat more primitive than Ursus deningeri. Therefore the bears of the Einhornhöhle Cave belong to the species "Ursus deningeri v. REICHENAU 1906". In the frontal teeth certain specializations occur. However, in view to the great ...